2017
DOI: 10.1186/s13071-017-1977-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk of travel-related cases of Zika virus infection is predicted by transmission intensity in outbreak-affected countries

Abstract: BackgroundZika virus (ZIKV) infection is emerging globally, currently causing outbreaks in the Caribbean, and Central and South America, and putting travellers to affected countries at risk. Model-based estimates for the basic reproduction number (R 0) of ZIKV in affected Caribbean and Central and South American countries, obtained from 2015 to 2016 human case surveillance data, were compared by logistic regression and Receiver-Operating Characteristic (ROC), with the prevalence of ZIKV-positive test results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
0
24
0
5
Order By: Relevance
“…Data suggests that sexual transmission alone is not likely to independently sustain an outbreak (30), and ongoing transmission is unlikely in the absence of tropical/subtropical Aedes spp. (32). The primary mosquito vectors-Aedes aegypti and Aedes albopictus-are not established in Canada and current research suggests that Canadian mosquito species are not competent hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data suggests that sexual transmission alone is not likely to independently sustain an outbreak (30), and ongoing transmission is unlikely in the absence of tropical/subtropical Aedes spp. (32). The primary mosquito vectors-Aedes aegypti and Aedes albopictus-are not established in Canada and current research suggests that Canadian mosquito species are not competent hosts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that the risk to travellers varies with the force of transmission cycles in the countries they are visiting, and that travellers as a group are not highly protected from infection in affected countries by virtue of their traveller status (32). The peak in cases recorded in July and August of 2016 was due to increases in cases exposed in Central America and the Caribbean, and to some extent from Mexico, but at a time when travel to these destinations are typically at their seasonal lows.…”
Section: Discussionmentioning
confidence: 99%
“…But a more detailed epidemiological link is needed between traveler force of infection and the scale of subsequent local outbreaks; so far, that causation has only been investigated in reverse. 44 The role of sexual transmission also requires deeper investigation. Early work suggested sexual transmission might be a substantial factor explaining the explosive South American outbreak 45,46 , but recent work has suggested sexually-transmitted outbreaks are unlikely 47 , even if sexual transmission increases the severity of vector-borne outbreaks 48 ; others still argue these risks are "understated."…”
Section: /19mentioning
confidence: 99%
“…Refugees, often from geographical areas where infectious diseases are more common and with different vaccination schedules and practices, may inadvertently bring these diseases into Canada (12). Tourism is also affected by climate change, as changes in both home and travel destinations influence the push and pull of factors motivating people to travel and the potential for disease spread (13)(14)(15). Vectors and pathogens can inadvertently be transported through shipments by air, land and sea (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Air travel has also been responsible for travellers carrying infections into new areas. In Canada, returning travellers have brought with them the Zika virus and have also sparked an outbreak of severe acute respiratory syndrome (SARS) coronavirus (15,21,22).…”
Section: Introductionmentioning
confidence: 99%